A Bibliometric Analysis of Asset-Backed Securities in Structured Finance - Judijanto, Loso (Westscience Press, 2025)
This study presents a comprehensive bibliometric analysis of the sustainable finance research landscape using data exclusively from the Scopus database and visualized through VOSviewer. By examining co-occurrence patterns, author networks, and international collaborations, the study uncovers major themes, influential contributors, and temporal developments in the field. The analysis identifies